Soil nematode communities on five oceanic islands across a latitudinal gradient in the north of the South China Sea: Influence of biotic and abiotic factors - Xionghui Liao (Elsevier, 2021)
Factors that influence the composition and diversity of soil nematode communities on oceanic islands are poorly understood. In this study, we evaluated the soil nematode communities and associated biotic and abiotic factors on five oceanic islands in the north of the South China Sea. We detected 38 nematode genera and found that bacterivores and fungivores were the dominant trophic groups, representing 54.2–70.4% and 15.1–35.3%, respectively, of total soil nematode abundance. The abundances of total soil nematodes and of all trophic groups, maturity, structure indices and nematode diversity were positively correlated with island latitude and area, and were negatively correlated with soil total K and annual temperature. In addition, the abundances of total soil nematodes, bacterivores, herbivores and nematode dominance index were positively associated with soil available K. The abundances of total soil nematodes, fungivores, herbivores, predators and omnivores, maturity, structure, Shannon diversity indices were positively related to soil moisture. Variation partitioning analysis showed that the combination of soil properties and climatic-geographical factors explained more of the variation (26.8–61.5%). The results suggest that larger island can maintain greater nematode diversity than smaller islands due to the greater diversity of habitats on larger island. The key climatic-geographical and edaphic factors affecting soil nematode communities were latitude, annual temperature, soil moisture and total K, respectively